(untitled) (IITM Journal of Business Studies, 2024)
India is experiencing extensive transformational changes in rural economy alongside transformations in its overall national economy. Conventionally, agriculture is judged as the leading segment of rural economy including rural employment in India. Frequent movement of workers between a variety of jobs and between informal and formal sections of rural economy have been observed in the past. (ILO Department of Statistics, 2011). Around forty per cent of land available for cultivation comprises of semi-arid tropics (SAT) where agriculture is generally a one-season activity. As a consequence, rural agricultural workers engage in rural non-farm activities within their village or else seasonally travel to urban cities to obtain employment.